The Role of Working Memory for Cognitive Control in Anorexia Nervosa versus Substance Use Disorder - Brooks, Samantha J.; Funk, Sabina G.; Young, Susanne Y.; Schiöth, Helgi B. (Frontiers in Psychology, 2017)
Prefrontal cortex executive functions, such as working memory (WM) interact with limbic processes to foster impulse control. Such an interaction is referred to in a growing body of publications by terms such as cognitive control, cognitive inhibition, affect regulation, self-regulation, top-down control and cognitive-emotion interaction. The rising trend of research into cognitive control of impulsivity, using various related terms reflects the importance of research into impulse control, as failure to employ cognitions optimally may eventually result in mental disorder. Against this background, we take a novel approach using an impulse control spectrum model - where anorexia nervosa (AN) and substance use disorder (SUD) are at opposite extremes - to examine the role of WM for cognitive control. With this aim, we first summarize WM processes in the healthy brain in order to frame a systematic review of the neuropsychological, neural and genetic findings of AN and SUD. In our systematic review of WM/cognitive control, we found n=15 studies of AN with a total of n=582 AN and n=365 HC participants; and n=93 studies of SUD with n=9106 SUD and n=3028 HC participants. In particular, we consider how WM load/capacity may support the neural process of excessive epistemic foraging (cognitive sampling of the environment to test predictions about the world) in AN that reduces distraction from salient stimuli. We also consider the link between WM and cognitive control in people with SUD who are prone to ‘jumping to conclusions’ and reduced epistemic foraging. Finally, in light of our review, we consider WM training as a novel research tool and an adjunct to enhance treatment that improves cognitive control of impulsivity.